If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = 3(x + -1) Reorder the terms: 10 + 2x = 3(x + -1) Reorder the terms: 10 + 2x = 3(-1 + x) 10 + 2x = (-1 * 3 + x * 3) 10 + 2x = (-3 + 3x) Solving 10 + 2x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + 2x + -3x = -3 + 3x + -3x Combine like terms: 2x + -3x = -1x 10 + -1x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + -1x = -3 + 0 10 + -1x = -3 Add '-10' to each side of the equation. 10 + -10 + -1x = -3 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -3 + -10 -1x = -3 + -10 Combine like terms: -3 + -10 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 10-2x=-8x+10 | | 5y+3y=27-y | | 2(x-4)=x-8 | | x^2-12x+8=5 | | 2x^3+7x^2-162x-567=0 | | 15-3x=3x | | 2(y+8)=3(y-2) | | A=b+8 | | 9x=22+7x | | -4x+24=-44 | | 4x-1=67+x | | 8-a-9=7a-6 | | -4x+24=-24 | | 7x-11=-67 | | 5-4x=-6x+5 | | 5z^3+15z^2= | | 6y^2-12y=gcf | | 2(x-5)-4=0 | | -6(x+1)-11=32+5 | | 9-2x=x-27 | | ln(x+11)-ln(x-3)=ln(3) | | 7(5c-1)-8=33c+7 | | 2x^4-4x^3-x^2+2x=gcf | | -24=21x | | -3x+5=-31-7x | | 3x+9=10y+8 | | 5z^3+15z^2+3z+9= | | 16x+4y=7 | | -56-2x=5x+7 | | 2x+-6+-4x+9=5x | | x(x+13)=x+10(x+1) | | y/5-9=-2 |